2021
DOI: 10.21833/ijaas.2021.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the levels of caffeine consumption among Saudi Arabian university students

Abstract: This study aimed to assess the caffeine consumption of Saudi Arabian undergraduate students and to determine if the average amount consumed is within healthful parameters. Caffeine consumption in Saudi Arabia is a major cultural and social feature. Consumption of excessive amounts of caffeine can be deleterious to the health of university students. This is a cross-sectional study. A total of 145 male undergraduate nursing students were surveyed using the Caffeine Consumption Questionnaire to assess their caffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…[10] Several cross-sectional investigations have been conducted in Saudi Arabia to assess the levels of caffeine consumption among different populations. These investigations were conducted in Riyadh, [11][12][13][14] Jeddah, [15] the northern borders, [16] and Madinah. [17] Among the identified studies that assessed preferred sources of caffeine, coffee was found to be favored.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[10] Several cross-sectional investigations have been conducted in Saudi Arabia to assess the levels of caffeine consumption among different populations. These investigations were conducted in Riyadh, [11][12][13][14] Jeddah, [15] the northern borders, [16] and Madinah. [17] Among the identified studies that assessed preferred sources of caffeine, coffee was found to be favored.…”
Section: Introductionmentioning
confidence: 99%
“…[17] Among the identified studies that assessed preferred sources of caffeine, coffee was found to be favored. [11,13,14] Among the studies that provided estimates of caffeine consumption, the mean daily consumption of caffeine varied between 424 mg [12] and 1599 mg per day. [11] According to the Department of Health in Canada and the US Food and Drug Administration, the recommended maximum daily intake of caffeine among adults was cited at 400 mg per day.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation